Collagen composition in equine exuberant granulation tissue reflects tissue immaturity - Lena Partusch; Catrin Sian Rutland; Ann Martens; Charis Du Cheyne; Ward De Spiegelaere; Jule Kristin Michler (PLoS ONE, 2025)
Exuberant granulation tissue (EGT) is a second intention wound healing disorder. It commonly occurs in the distal limb of horses. EGT causes significant increase in the duration and cost of treatment, potentially leading to the decision not to pursue treatment and euthanize the patient. The underlying pathomechanisms of this fibroproliferative disorder remain unclear, particularly in terms of collagen composition and the association between myofibroblasts and blood vessels. This study investigated the collagen composition in naturally occurring EGT following trimming in 19 horses (EGT group). In both the superficial and deep wound beds of EGT-affected horses, the collagen distribution was assessed and compared to control wounds (n = 6 horses, control group, punch biopsies) using histology. Immunofluorescence was performed to colocalize activated alpha smooth muscle actin-positive myofibroblasts in EGT as well as angiogenic markers. Our histological findings showed significantly higher amounts of immature collagen (type III) in the superficial and deep regions of EGT compared to the controls while the total amount of collagen in both groups did not differ significantly. In EGT, occluded microvessels and endothelial cell hypertrophy were present in the deep layer and myofibroblasts were ubiquitously found in the whole wound bed. Markers for intermediate filaments were reduced in the superficial region. In conclusion, collagen composition in EGT differed significantly from control wounds, indicating tissue immaturity. Consequently, promoting tissue maturation towards a more mature ECM composition could serve as a valuable target for future therapeutic interventions enabling better regeneration.